PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. MURNI PUTRAMAS DEPOK - Ryan Gunadi; Tri Wartono (Journal of Research and Publication Innovation, 2025)
This study aims to find out and analyze how the Influence of Competence and Work Motivation on Employee Performance of PT. Murni Putramas Depok. The method used in this study is a quantitative method, namely through the distribution of questionnaires to 52 employees at PT. Murni Putramas Depok, data collection and data analysis use statistics. The population and sample in this study amounted to 52 employees. The analysis methods used in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, determination coefficient test and significance test (t test and F test). The results of this study show that the results of the partial test (t-test) of Competency have a positive and significant effect on employee performance with a significance value of less than 5% (0.000 < 0.05) and supported by the t-value calculated > t table (3,868 > 1,677), Work Motivation has a positive and significant effect on employee performance with a significance value of less than 5% (0.000 < 0.05) and supported by the t-value calculated > t table (4,117 > 1,677). The results of the F test show that Competence and Work Motivation have a positive and significant effect together on employee performance with a significant value of less than 0.05 or 0.000 < 0.05, and supported by an F value of 38,603 where the F value is greater than the F table or 38,603 > 3,190. The results of the determination coefficient test showed that the Adjusted R Square was 0.596 or 59.6%. This shows that the percentage of influence of motivation and work discipline on performance is 59.6%.